Escherichia coli DNA repair genes radA and sms are the same gene. - Song, Y (1996)
Escherichia coli strains carrying radA100 or sms mutations were identical in their sensitivities to either methyl methanesulfonate or UV radiation treatment and in their plasmid complementation patterns for UV radiation survival. DNA sequencing analysis of the radA mutant and radA+ strains and comparison of their sequences with the published sms gene sequence showed the radA mutant to differ only by a G-to-A transition mutation, which is predicted to change a cysteine in a zinc-finger motif to tyrosine. The sms gene is concluded to be identical to the previously described radA gene.